Effect of PLGA-IB on ICAM-1 and VCAM-1 expression in a mice adhesion model - Jamshidi-Adegani, Fatemeh; Seyedjafari, Ehsan; Gheibi, Nematollah; Dodel, Masumeh; Mohammadi-Sangcheshmeh, Abdollah; Soleimani, Masoud; Sahmani, Mehdi (Novelty in Biomedicine, 2016)
Background: In this study, we compared the effect of ibuprofen (IB) while incorporating by Poly Lactic-co-Glycolic Acid (PLGA) nanofiber on expression of adhesion molecules ICAM-1 and VCAM-1 in a mice adhesion model. Materials and Methods: Using an adhesion model were induced in mice, PLGA-IB and PLGA membranes and IB were sutured between the abdominal wall and peritoneum after surgical operation to reveal the best membrane for prevention of postoperative adhesion bands by comparison of ICAM-1 and VCAM-1 expression. Results: Compared with other groups, PLGA-IB showed a greater ability to reduce ICAM-1 and VCAM-1 expression. Conclusion: These results suggested that in considering the FDA approved polymers, PLGA-IB could be introduced as a potential candidate for prevention of abdominal post-surgery inflammation and adhesion band formation after surgeries.